SISTEMIKNYA PRIVATISASI BADAN USAHA MILIK NEGARA DAN SUMBER DAYA ALAM DI INDONESIA - Syafi’ie, M. (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
Privatization policy has been the trend, especially in developing countrie. The presence of international economic institutions such as the IMF and World Bank have a big impact that drives policy. Privatization is the ideology of neoliberalism that requires complete freedom of the free market, and encourage individual ownership of the public assets. Currently, Indonesia has become a part of the ideological hegemony of neoliberalism. Systemic Privatisation occurs. The impact is even more alarming: environmental degradation, land conflicts, poverty, and natural disasters. Privatization is likely negative, can not be separated from the historical study of Islamic law. In Islamic law, privatization is not justified, because there are provisions in the Al-Quran and Al-Hadits which prohibits the individual ownership (privatization) of the treasures that are public.